In-silico analysis of non-synonymous single nucleotide polymorphisms in human β-defensin type 1 gene reveals their impact on protein-ligand binding sites. (June 2022) - Fareed, Muhammad Mazhar; Ullah, Sana; Aziz, Shan; Johnsen, Todd Axel; Shityakov, Sergey
Abstract: Single nucleotide polymorphism (SNPs) is an important genetic biomarker to assess protein function and its possible contribution to genetic diseases, such as the β- defensin 1 gene (DEFB1)-associated non-synonymous SNPs (nsSNPs). Defensins are antimicrobial and immunomodulatory peptides, acting as part of innate immunity, and killing bacteria by interacting phosphatidylinositol 4, 5-bisphosphate (PIP2). Therefore, we apply cutting-edge computational algorithms to identify detrimental SNPs in the DEFB1 gene that potentially impact PIP2 binding sites. Furthermore, 4 most important nsSNPs in the DEFB1 gene were discovered (C67S, T58S, G62W, and Y35C) and only two of them were found to be linked to the PIP2 binding site-forming residues (Thr58 and Tyr35). Additional molecular docking and molecular dynamics simulations confirmed the decreased binding affinity of DEFB1 to bacterial PIP2 due to these mutations. Overall, this computational study analyzing nsSNPs in DEFB1 provides more understanding of how these missense mutations could impair or change protein functions by altering the PIP2 binding site. Graphical Abstract: ga1 Highlights: Defensins (DEF) kill bacteria by interacting with phosphatidylinositol 4, 5-bisphosphate (PIP2). Single nucleotide polymorphism (SNPs) in DEF gene impairs protein function to bind PIP2. Most of predicted SNPs show no significant effect on DEF stability except for G62W. Some SNPs (Y35C and T58S) found to be associated with PIP2 binding site.